PELATIHAN DAN PENDAMPINGAN PEMBUATAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS KURIKULUM MERDEKA DI SMPN 3 SUNGAI KAKAP - Matsun Matsun; Ryan Permana; Adhitya Prihadi (Jurnal Abdi Insani, 2022)
The learning process in the new normal period of the COVID-19 pandemic has greatly impacted the world of education. The problem of the learning process is the main problem at SMPN 3 Sungai Kakap, Kubu Raya Regency. The purpose of this PKM activity is that teachers of SMPN 3 Sungai Kakap are able to make Student Worksheets (LKPD) based on an independent curriculum through training and mentoring and to know the effectiveness of PKM activities. The method used in this service is a user requirement approach (adjusting to the needs of users), namely through training (workshops) and mentoring as well as a team of proposers and partners who are proactively involved in every activity. The results of the training and mentoring activities for making LKPD are 100% of the participants present can make LKPD, and partner satisfaction in the PKM activities carried out is 86.32 with the criteria strongly agreeing with the details: 1) PKM topics are relevant to the needs of partners with a score of 86.842%, 2) The planned PKM activity schedule is in accordance with the realization in the field with a score of 80.263%, 3) The PKM team involved in PKM activities has a polite, friendly, and cooperative attitude with a score of 90.789%, 4) The PKM team involved in PKM has expertise according to the topic of PKM carried out with a score of 85.526 % ,5) The PKM team has a responsive attitude to any complaints/questions/problems submitted by PKM partners with a score of 88.158 %, 6) Cooperation with partners in PKM activities has been implemented using cooperative, consultative principles and corrective with a score of 85.526%, 7) PKM cooperation activities are useful according to the needs of partners with a score of 88.158%, 8) Activities PKM increases the knowledge/skills of partners with a score of 86.842%, 9) The final report of the results of cooperation activities in the PKM sector has been prepared and communicated to partners with a score of 85.526%, and 10) Follow-up of PKM activities with partners is useful for planning the next activity by score 85.526%. Based on the activities that have been carried out, it can be concluded that the PKM team has carried out the workshop well, smoothly, and fun because all teachers can make LKPD that is interesting and based on local wisdom.